Kontrak Usaha Pemanfaatan Wisata Alam pada Kesatuan Pengelolaan Hutan Lindung Rinjani Barat - Muhammad Rifqi Tirta Mudhofir; Bramasto Nugroho; Sudarsono Soedomo (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Partnership in natural tourism utilization of protected forests area can increase the forests value, but also has a risk of damage to forest areas managed by KPHL Rinjani West (FMU). The relationship between FMU and partners can be seen as a principal-agent relationship that may have problems as adverse selection, asymmetric information, moral hazard and agency costs. The results of policy analysis, field observation, and in-depth interviews with related parties indicate that some policies provide different partnership schemes with its own advantages. Benefit by each party needs to be followed by appropriate role in partnership. Increased revenues and changes in the beneficiary system can raise potential revenue for KPH and partners.